Odpowiedź:
A) -6x + 2y +1
B) 19a -13b +28
Zad 5A 292,5
Zad 5B 5x - 5y
Szczegółowe wyjaśnienie:
A) - (2x + 3y - 2) + (-4x + 5y - 1) = -2x -3y + 2 - 4x +5y - 1 = -6x + 2y +1
B) -3(-5a + 3b - 4) + 2(-2a - 2b + 8) = - (-15a + 9b - 12) + (4a - 4b + 16) = 15a -9b +12 +4a -4b +16 = 19a -13b +28
Zad. 5 A
[tex]\frac{1}{2} (-2ab^{3} ) + \frac{2}{3} (9a^{2} b) = -\frac{2ab^{3} }{2} + \frac{2*9a^{2}b }{3} = -ab^{2} +\frac{18a^{2}b }{3} = -ab^{2} +6a^{2} b[/tex]
[tex]a= -8, b=\frac{3}{4}[/tex]
[tex]-(-8 )* (\frac{3}{4})^{2} + 6*(-8^{2} )*\frac{3}{4} = 8*\frac{9}{16} + 6* 64 *\frac{3}{4} =\frac{72}{16} +\frac{6* 64 *3}{4} = \frac{18}{4} +\frac{1152}{4} =\frac{1170}{4} =292\frac{2}{4} =292\frac{1}{2}[/tex]
Zad. 5 B
4( x - y) - (-x + y) = 4x - 4y + x - y = 5x - 5y